Central Bank control of external transfers and its impact on the tax information system: Applied research in the General Authority for Taxes (Journal of Accounting and Financial Studies ( JAFS ), 2019)
Tax information system is one of the most important means that help the tax administration to reach the real income of the taxpayer, and the problem of research came in the General Authority for Tax ,The next question (Does the control carried out by the Central Bank on foreign remittances to reach the real income of the taxpayer). The research is gaining importance by focusing on the Central Bank's control over foreign remittances, and how to use this control to finance the tax information system. The relationship between the Central Bank's control over foreign remittances and the tax information system.The study has reached a number of recommendations, the most important of which are the following: The work of an integrated information system linking the General Tax Authority with the Central Bank, through which the General Authority for Taxes is provided with all the external remittance information allocated for import through the currency window. The parties accepted the guilty person in order to reduce the phenomenon of tax evasion and the phenomenon of foreign currency smuggling.